Use of the internal standardization for difficult sampling by graphite furnace atomic absorption spectrometry - Oliveira, Adriana P. [UNESP]; Gomes Neto, José Anchieta [UNESP]; Nóbrega, Joaquim A.; Oliveira, Pedro V. (Elsevier, 2004)
This work shows the potentiality of As as internal standard to compensate errors from sampling of sparkling drinking water samples in the determination of selenium by graphite furnace atomic absorption spectrometry. The mixture Pd(NO 3) 2/Mg(NO 3) 2 was used as chemical modifier. All samples and reference solutions were automatically spiked with 500 μg l -1 As and 0.2% (v/v) HNO 3 by the autosampler, eliminating the need for manual dilutions. For 10 μl dispensed sample into the graphite tube, a good correlation (r=0.9996) was obtained between the ratio of analyte absorbance by the internal standard absorbance and the analyte concentrations. The relative standard deviations (R.S.D.) of measurements varied from 0.05 to 2% and from 1.9 to 5% (n=12) with and without internal standardization, respectively. The limit of detection (LD) based on integrated absorbance was 3.0 μg l -1 Se. Recoveries in the 94-109% range for Se spiked samples were obtained. Internal standardization (IS) improved the repeatability of measurements and increased the lifetime of the graphite tube in ca. 15%. © 2004 Elsevier B.V. All rights reserved.
Keywords: Complex matrices; Graphite furnace atomic absorption spectrometry; Internal standardization; Sparkling waters; Absorption; Arsenic; Concentration (process); Furnaces; Potable water; Standardization; Atomic absorption spectrometry; Chemical modifiers; Graphite furnace; Graphite; arsenic; graphite; magnesium nitrate; nitric acid derivative; palladium complex; selenium; unclassified drug; absorption; atomic absorption spectrometry; correlation analysis; dilution; electrochemical analysis; reproducibility; sampling; temperature sensitivity